Selective occlusion of the hepatic artery and portal vein improves liver hypertrophy for staged hepatectomy - Changku Jia; Ke Ge; Sunbing Xu; Ling Liu; Jie Weng; Youke Chen (World Journal of Surgical Oncology, 2019)
Abstract Background To evaluate the safety and feasibility of selective occlusion of the hepatic artery and portal vein (SOAP) for staged hepatectomy (SOAPS) in patients with hepatocellular carcinoma (HCC) Methods From December 2014 to August 2018, 9 patients with unresectable HCC were chosen to undergo SOAPS. SOAP without liver partition was performed in the first stage. The second stage was performed when future liver remnant (FLR) was equal to or bigger than 40% of the standard liver volume (SLV). The growth rate of FLR, perioperative outcomes, and survival data was recorded. Results In the first stage, all the 9 patients completed SOAP. Two cases received radiological interventional method and 7 cases received open operation. None of them developed liver failure and died following SOAP. After SOAP, FLR increased 145.0 ml (115.0 to 210 ml) and 37.1% (25.6 to 51.7%) on average. The average time interval between the two stages was 14.1 days (8 to 18 days). In the second stage, no in-hospital deaths occurred after SOAPS. One patient suffered from liver failure after SOAPS, and artificial liver support was adopted and his total bilirubin level returned to normal after postoperative day 35. The alpha-fetoprotein level of 8 patients reduced to normal within 2 months after SOAPS. Among 9 patients, 5 patients survived, 4 patients died of intrahepatic recurrence, lung metastasis, or bone metastasis. In the 5 survived cases, bone metastasis and intrahepatic recurrence were found in 1 patient, intrahepatic recurrence was found in another patient, and the remaining 3 patients were free of recurrence. The median disease-free survival time and overall survival time were 10.4 and 13.9 months, respectively. Conclusion SOAP can facilitate rapid and sustained FLR hypertrophy, and SOAPS is safe and effective in patients with unresectable HCC.